URGENSI KETERWAKILAN DAERAH DALAM KOMPOSISI KABINET - Muhammad Erfa Redhani (Belom Bahadat, 2019)
Regional representation in the composition of the cabinet has not become an important part in the state administration tradition in Indonesia. Whereas regional representation is part of the way to bring together the values ​​of unity and integrity in the Unitary State of the Republic of Indonesia. The president's authority to appoint and dismiss ministers is a prerogative right granted by the 1945 Constitution to a president. With the condition of Indonesia which has a multi-party party system, the president's consideration is often in determining cabinet officials with only two considerations, namely political considerations and professional considerations or often called zaken cabinet. Meanwhile, the aspect of regional representation is not an important part in the president's consideration. This study wants to answer the urgency of regional representation in the composition of the cabinet and how the design of ministerial recruitment that represents cabinet representation. The results of this study indicate that regional representation in the composition of the cabinet is very important in terms of the aspect of orginal intent in the formulation of the 1945 Constitution. In addition, aspects that should be considered